An image-based method to quantify biomechanical properties of the rectum in radiotherapy of prostate cancer. (21st October 2015) - Casares-Magaz, Oscar; Thor, Maria; Liao, Donghua; Frøkjær, Jens B.; Kræmer, Pia; Krogh, Klaus; Drewes, Asbjørn M.; Gregersen, Hans; Moiseenko, Vitali; Høyer, Morten; Muren, Ludvig P.
ABSTRACT: Background . Gastrointestinal morbidity after radiotherapy (RT) for prostate cancer may be related to the biomechanical properties of the rectum. In this study we present a magnetic resonance imaging (MRI)-based method to quantitate the thickness and elasticity of the rectal wall in prostate cancer patients treated with RT. Material and methods . Four patients previously treated with RT for prostate cancer underwent an MRI session with stepwise rectal bag deflation (from a maximum tolerable volume to 0 ml, in 50 ml steps), with a probe inserted inside the bag to monitor the internal rectal pressure. MRIs were acquired using Dixon sequences (4 mm axial slice thickness) at each deflation step. Rectal walls were defined from the recto-sigmoid junction to 3 cm above the anal canal as the space between the inner and outer wall surfaces. The wall thickness was determined and biomechanical properties (strain and stress) were calculated from the pressure measurements and the MRI-segmented rectal walls. Results . The integral rectal pressure varied for the maximum tolerable volume (range 150–250 ml) across patients and ranged from 1.3 to 4.0 kPa (SD = 1.2 kPa). Wall thickness was found to vary between patients and also across different rectum segments, with a mean (SD) thickness for the different segments at the 50 ml distension volume of 1.8–4.0 (0.6) mm. Stress showed larger variation than strain, with mean (SD) values for the different segments ranging between 1.5 and 7.0 (1.5) kPa. Conclusion . We have developed a method to quantify biomechanical properties of the rectal wall. The resulting rectal wall thickness, strain and stress differed between patients, as well as across different rectal wall sections. These findings could provide guidance in future predictive outcome modelling in order to better understand the rectal dose-volume response relationship.